A flexible lab-on-a-chip for the synthesis and magnetic separation of magnetite decorated with gold nanoparticles - Cabrera, Flavio C. [UNESP]; Melo, Antonio F. A. A.; Souza, Joao C. P. de; Job, Aldo E. [UNESP]; Crespilho, Frank N. (Royal Soc Chemistry, 2015)
Magnetite decorated with gold nanoparticles (Fe3O4-AuNPs) is a ferrimagnetic material with unprecedented applications in immunosensors, as a contrast agent for imaging diagnosis, and for the photothermal ablation of tumor cells. Here, we show the preparation of controlled amounts of Fe3O4-AuNPs without organic solvents, surfactants, or heat treatment. For this, we have developed a customized natural-rubber-based microfluidic device (NRMD) as a flexible lab-on-a-chip for the decoration of Fe3O4 with AuNPs. With a novel NRMD configuration, monodisperse Fe3O4-NPs (phi = 10 nm) decorated with AuNPs (phi = 4 nm) were readily obtained. The AuNPs were homogenous in terms of their size and their distribution on the Fe3O4-NP surfaces. Furthermore, the lab-on-a-chip was projected with an internal system for magnetic separation, an innovation in terms of aqueous/carrier phase separation. Finally, the nanomaterials produced with this NRMD are free of organic solvents and surfactants, allowing them to be used directly for medical applications.